PENGARUH MOTIF HEDONIS DAN PROMOSI DI MEDIA SOSIAL TERHADAP PEMBELIAN IMPULSIF - Putri, Pinky Greciela Veronica; Anggraeni, Rila (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
The objective of this research is to identify the effect of hedonic motivation and social media promotion on the impulsive buying of Shopee users. This study is categorized as explanatory research that is used to develop and validate causal relationship between variables through hypothesis testing. The samples were selected using non-probability sampling method and purposive sampling technique with the criteria of individuals with the minimum age of seventeen years who live in Malang city and use Shopee application, resulting in 120 respondents. The data of this research was harvested from Likert-scaled questionnaires, which were assessed using validity and reliability testing, and was analyzed in SPSS 25. The hypotheses were examined using t test. This study finds that hedonic motivation and social media promotion simultaneously and partially have significant effects on impulsive buying. Furthermore, hedonic motivation has the most dominant effect since it has the highest beta coefficient and t-score. The findings imply that Shopee can increase their sales by conducting social media promotion.